2013
DOI: 10.1088/0957-0233/24/7/074012
|View full text |Cite
|
Sign up to set email alerts
|

Tracking lung tumour motion using a dynamically weighted optical flow algorithm and electronic portal imaging device

Abstract: This paper investigates the feasibility and accuracy of using a computer vision algorithm and electronic portal images to track the motion of a tumour-like target from a breathing phantom. A multi-resolution optical flow algorithm that incorporates weighting based on the differences between frames was used to obtain a set of vectors corresponding to the motion between two frames. A global value representing the average motion was obtained by computing the average weighted mean from the set of vectors. The trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Besides DL-based approaches, numerous other studies have investigated non-DL-based image tracking techniques for markerless lung tumor tracking, including well-established methods such as image registration, 40 template matching, 41 and optical flow 42,43 . Other less common methods like short arc tumor tracking 44 and hidden Markov model 45 have also been proposed.Some studies were exclusively conducted on digital or experimental phantoms with tumor motions that were mechanically controlled following either simulated breathing patterns 42 or patient-measured motion traces. 45,46 They were often able to achieve sub-millimeter accuracy, which might potentially be biased by the often simpler geometry of phantom anatomy and tumor shape/size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides DL-based approaches, numerous other studies have investigated non-DL-based image tracking techniques for markerless lung tumor tracking, including well-established methods such as image registration, 40 template matching, 41 and optical flow 42,43 . Other less common methods like short arc tumor tracking 44 and hidden Markov model 45 have also been proposed.Some studies were exclusively conducted on digital or experimental phantoms with tumor motions that were mechanically controlled following either simulated breathing patterns 42 or patient-measured motion traces. 45,46 They were often able to achieve sub-millimeter accuracy, which might potentially be biased by the often simpler geometry of phantom anatomy and tumor shape/size.…”
Section: Discussionmentioning
confidence: 99%
“…Besides DL‐based approaches, numerous other studies have investigated non‐DL‐based image tracking techniques for markerless lung tumor tracking, including well‐established methods such as image registration, 40 template matching, 41 and optical flow 42,43 . Other less common methods like short arc tumor tracking 44 and hidden Markov model 45 have also been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al [ 14 ] have reported DXR had the potential to visualize vector-field of lung motion using the cross-correlation method. OFM was initially proposed as one of the markerless tracking methods for lung tumors in chest radiographs [ 26 ]. OFM can visualize motion velocity with higher spatial resolution than the cross-correlation method [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although neural networks and fuzzy logic exhibit a satisfactory performance, in the research conducted with the use of these techniques, only 3 and 20 patients were tested, respectively [18,20,21]. In the work presented by Teo et al, only the tumor motion in the superior-inferior direction was predicted with the input of internal target position with an electronic portal imaging device (EPID) at the frequency at 7.5 Hz [19,22]. In addition, their approach cannot be performed if the internal target positions are invisible on EPID.…”
Section: Introductionmentioning
confidence: 99%